The 'Informality Gap': Can Education Help Minorities Escape Informal Employment? Evidence from Peru - Juan Gabriel Delgado Montes; Javier Corrales; Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
Discrimination in formal labor markets can push discriminated groups into labor informality, where wages are lower and pensions scarce. In this paper, we explore whether education offsets discrimination by empowering discriminated groups to successfully compete for formal jobs. Specifically, we calculate the returns to education on formal employment for a discriminated group (indigenous Peruvians). We find that certain education levels –primary and tertiary–allow indigenous workers equal access to formal jobs. But, for indigenous workers with only secondary education, we find an "informality trap" where returns to secondary education are 6.7 percentage points lower, a difference larger than the net returns of primary education. We find that differences in education quality across districts, more than migration and industry-specific patterns, are the main drivers of this effect. These findings have policy implications suggesting improvements to quality are essential for secondary education to empower discriminated groups to successfully compete in labor markets.
Keywords: E26; J46; I26; H55; J71; 330; exclusion; social security; informal labor markets; education; Latin America